Website Creation Application Used Car Sales Using Macromedia Dreamweaver 8.0, PHP and MySQL - Heru Setyawan; Munich Heindari Eka Sari , SKom, MMSI (Jurnal Sistem Informasi, 2010)
Rapidly evolving information technology is getting easier every time  people in getting information. The Internet is a quick and easy to transmit the information to reach the wider community.  Use o f website is very useful in trying to offer and informed used car sales to consumers. Everything is presented in website page views are easily understood by consumers, ranging from the main menu to search for used cars based on the specific physical form,t ype, and the desired price of the car.  Macromedia Dreamweaver 8.0, PHP and MySQL are a few examples of  many software that can solve the problem.